Environmental drivers and transcriptomic variations shaping Lei bamboo shoots across cultivation regions - Qian, Yingzhai; Jia, Jingyi; Chen, Zhenlin; Wang, Kecheng; Li, Peng; Gao, Peijun; Ying, Yeqing; Shi, Wenhui (Frontiers in Plant Science, 2025)
The nutritional composition of bamboo shoots varies significantly across regions, yet the precise environmental drivers and underlying molecular mechanisms remain poorly understood. In particular, the influence of soil properties and climatic factors on key metabolic pathways regulating bamboo shoot quality has not been systematically examined. In this study, we investigate the environmental determinants of nutrient accumulation in Lei bamboo (Phyllostachys violascens) shoots by integrating environmental analysis, nutritional profiling, and transcriptomics. We identified soil organic matter, total porosity, and longitude as the primary factors influencing bamboo shoot nutrition, with higher soil organic matter correlating with enhanced nutrient content. Transcriptome analysis revealed that environmental conditions regulate key metabolic pathways, including starch metabolism (e.g., BGLU, SPS) and flavonoid biosynthesis (e.g., PAL, 4CL), ultimately shaping bamboo shoot quality. Based on these findings, we developed a predictive model linking environmental factors, gene expression, and nutritional traits, providing a foundation for precision cultivation strategies. This study provides novel insights into plant-environment interactions governing bamboo shoot nutrition and offers actionable strategies for region-specific cultivation, aligning with consumer demand for healthier bamboo-based products.